Drug-coated balloons for small coronary artery disease (BASKET-SMALL 2): an open-label randomised non-inferiority trial. Issue 10150 (8th September 2018) - Jeger, Raban V; Farah, Ahmed; Ohlow, Marc-Alexander; Mangner, Norman; Möbius-Winkler, Sven; Leibundgut, Gregor; Weilenmann, Daniel; Wöhrle, Jochen; Richter, Stefan; Schreiber, Matthias; Mahfoud, Felix; Linke, Axel; et al.
Summary: Background: Drug-coated balloons (DCB) are a novel therapeutic strategy for small native coronary artery disease. However, their safety and efficacy is poorly defined in comparison with drug-eluting stents (DES). Methods: BASKET-SMALL 2 was a multicentre, open-label, randomised non-inferiority trial. 758 patients with de-novo lesions (<3 mm in diameter) in coronary vessels and an indication for percutaneous coronary intervention were randomly allocated (1:1) to receive angioplasty with DCB versus implantation of a second-generation DES after successful predilatation via an interactive internet-based response system. Dual antiplatelet therapy was given according to current guidelines. The primary objective was to show non-inferiority of DCB versus DES regarding major adverse cardiac events (MACE; ie, cardiac death, non-fatal myocardial infarction, and target-vessel revascularisation) after 12 months. The non-inferiority margin was an absolute difference of 4% in MACE. This trial is registered withClinicalTrials.gov, numberNCT01574534 . Findings: Between April 10, 2012, and February 1, 2017, 382 patients were randomly assigned to the DCB group and 376 to DES group. Non-inferiority of DCB versus DES was shown because the 95% CI of the absolute difference in MACE in the per-protocol population was below the predefined margin (−3·83 to 3·93%, p=0·0217). After 12 months, the proportions of MACE were similar in both groups of the full-analysis population (MACE was 7·5% for the DCB group vs 7·3% for the DES group; hazard ratio [HR] 0·97 [95% CI 0·58–1·64], p=0·9180). There were five (1·3%) cardiac-related deaths in the DES group and 12 (3·1%) in the DCB group (full analysis population). Probable or definite stent thrombosis (three [0·8%] in the DCB group vs four [1·1%] in the DES group; HR 0·73 [0·16–3·26]) and major bleeding (four [1·1%] in the DCB group vs nine [2·4%] in the DES group; HR 0·45 [0·14–1·46]) were the most common adverse events. Interpretation: In small native coronary artery disease, DCB was non-inferior to DES regarding MACE up to 12 months, with similar event rates for both treatment groups. Funding: Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung, Basel Cardiovascular Research Foundation, and B Braun Medical AG.